An Integrated Analysis of Radial Spoke Head and Outer Dynein Arm Protein Defects and Ciliogenesis Abnormality in Nasal Polyps - Zi, Xiao-xue; Guan, Wei-jie; Peng, Yang; Tan, Kai Sen; Liu, Jing; He, Ting-ting; Ong, Yew-kwang; Thong, Mark; Shi, Li; Wang, De-yun (Frontiers in Genetics, 2019)
Background: Nasal polyp (NP) is a chronic upper airway inflammatory diaease that is frequently triggered by defective host-defense. However, the mechanisms underlying the impaired barrier function such as cilia-mediated mucociliary clearance remain poorly understood. Objective: To assess ciliary ultrastructural and ciliogenesis marker expression and the phenotypes of ciliated cells in NP. Methods: NP biopsy samples were obtained from 97 NP patients and inferior turbinate from 32 healthy controls. Immunofluorescence staining, quantitative polymerase chain reaction and single-cell cytospin staining were performed. We classified the patterns of radial spoke head protein (RSPH) 1, 4A (RSPH4A), 9 (RSPH9) and dynein axonemal heavy chain 5 (DNAH5) localization. A semi-quantitative scoring system was developed to assess their expression patterns and associations with ciliogenesis markers [centrosomal protein 110 (CP110) and forkhead box j1 (FOXJ1)]. Results: Median scores of RSPH1, RSPH4A, RSPH9 and DNAH5 were significantly higher in NP than in healthy controls, particularly in eosinophilic NPs. Expression pattern scores of RSPH1, RSPH4A, RSPH9 and DNAH5 correlated positively with each other in both groups. In primary-cell specimens, abnormal expression patterns were significantly more common in NP. The total fluorescence intensity of CP110 and FOXJ1 was significantly higher in NPs and correlated positively with expression pattern scores of RSPH1, RSPH4A, RSPH9 and DNAH5. A trend towards lengthened cilia was observed in NP. Conclusion: In the chronic airway inflammatory milieu, the up-regulated ciliogenesis correlates with the abnormal expression of ciliary ultrastructural markers (i.e., DNAH5) in NP (particularly eosinophilic NP).